2016
DOI: 10.1051/alr/2016024
|View full text |Cite
|
Sign up to set email alerts
|

Target strength estimates of red emperor (Lutjanus sebae) with Bayesian parameter calibration

Abstract: Red emperor (Lutjanus sebae) is a long-lived tropical demersal snapper which is widely distributed in the Western Pacific and Indian Ocean. Despite the commercial and recreational importance of the species for the Northern Demersal Scalefish Fishery off the Northwest coast of Western Australia, we still lack a thorough understanding of its distribution and abundance in the area. To better understand the acoustic scattering properties of red emperor its acoustic backscattering characteristics were modelled base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Acoustic parameters, such as the density contrast (g) and sound speed contrast (h), were needed in this model. Previous researchers found that fish flesh had g values ranging from ~1.02 to 1.06 and h values from ~1.02 to 1.08 (Love, 1978;Medwin and Clay, 1998;Gastauer et al, 2016). Typical acoustic parameters of fish with a swim bladder, measured using Atlantic cod (Gadus morhua), from literature (Clay and Horne, 1994) were chosen in our model (Table 1), which were also used in the jack mackerel (Trachurus japonicus) TS research performed by Hwang et al (2015).…”
Section: Ts Estimationmentioning
confidence: 99%
“…Acoustic parameters, such as the density contrast (g) and sound speed contrast (h), were needed in this model. Previous researchers found that fish flesh had g values ranging from ~1.02 to 1.06 and h values from ~1.02 to 1.08 (Love, 1978;Medwin and Clay, 1998;Gastauer et al, 2016). Typical acoustic parameters of fish with a swim bladder, measured using Atlantic cod (Gadus morhua), from literature (Clay and Horne, 1994) were chosen in our model (Table 1), which were also used in the jack mackerel (Trachurus japonicus) TS research performed by Hwang et al (2015).…”
Section: Ts Estimationmentioning
confidence: 99%
“…The minimum TS can be derived from in situ measurements (e.g. Gastauer et al, 2016), ex situ distributions or theoretical models. This procedure has been implemented in commercial software (see Parker-Stetter et al, 2009, for details).…”
Section: Introductionmentioning
confidence: 99%
“…Shape input information for such models require an accurate representation of a real swimbladder shape which can be obtained by the dissection of the species 28 or by means of X-ray scan 29,30 . Even more detailed images can be obtained through Computer Tomography scans (CT) and Magnetic resonance imaging (MRI) 31,32 . These techniques are now in use for the implementation of approximation models such as the deformed cylinder model (DCM), and Kirchhoff Ray Mode model (KRM) 33,34 , along with complex numerical models that solve wave equations on finite surface elements, such as the Boundary Element Method (BEM) and the Finite Element Method (FEM) 35,36 .…”
Section: Introductionmentioning
confidence: 99%